Penerapan Model Pembelajaran Think Pair Share (TPS) Terhadap Rasa Percaya Diri Siswa SDN Pasanggrahan 1 - Rijal Agustian; Imas NurhidayatiAisyah (Study Program of Madrasah Ibtidaiyah Teacher Education at Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2025)
The challenge in education that must be faced in the 21st century is the need for different skills from each student. Applying the Think Pair Share (TPS) learning model to students' self-confidence can create inclusive learning. This research aims to determine the significance of the influence of the Think Pair Share (TPS) learning model on students' self-confidence at SDN Pasanggrahan 1. This research uses a quasi-experimental method with a nonequivalent control group design. Sampling was carried out using a purposive sampling technique. Researchers used a control group and an experimental group with 22 students. The experimental class uses the Think Pair Share (TPS) method while the control class uses the conventional method. The instruments used in this research were questionnaires and observations. The data obtained was analyzed using SPSS version 26. The results of this study showed a value of 0.000 > 0.05, which means that there is a significant influence between the Think Pair Share (TPS) learning model on students' self-confidence. It can be concluded that there is an influence of the Think Pair Share (TPS) learning model on the self-confidence of students at SDN Pasanggrahan 1.